Mobile Money Use In Ghana: An Assessment Of Its Relevance In The Financial Inclusion Of Rural Communities - Fiasorgbor, Doris Ama Floria; Caroline, Tettey (Advances in Social Sciences Research Journal, 2017)
Mobile money offers new possibilities for making financial services more inclusive in Africa, especially in rural Africa. Unlike conventional banking and financial services, mobile network operators (MNOs) have made huge investments to create networks that reach further and deeper into rural areas historically marginalized in an effort to satisfy their demand to communicate. Infrastructure changes in rural areas are external factors that may force new models for the mobile services. Since 2005, a new technology—mobile money—has become available in over eighty (80) countries worldwide. Mobile money (m-money) is a product that allows clients to use text messages to store value in an account accessible by the handset, convert cash in and out of the stored value account, and transfer value between users. As compared with the traditional means of sending and receiving money within many developing countries, such as Western Union and MoneyGram, the postal service or delivery by friends or family, m-money substantially reduces the costs of transferring money. M-money offers a new potential mechanism for increasing the financial inclusion of the world’s poor. The main objective of this investigation is to critically examine mobile money usage and its relevance in the financial inclusion of rural communities. The generally attained educational level by the participants is Junior high school/Middle school qualification. Deposits, withdrawals (cash-in and cash-out), fund transfers and airtime purchase were the most patronised services. Results from the focused group discussion (FGDs) also showed that participants had used the mobile money services and the most used services were the funds transfer (receiving remittances) and buying airtime. The study also found that most of the participant sent and received mobile money compared to those that had either only sent or only received. Mobile money service has improved the financial inclusion of rural folk as demonstrated by the access and use of mobile money by the rural people. The researchers recommend that mobile money service providers should educate rural people to save through mobile money service.